Trabalho de campo em geografia: relato de uma atividade na disciplina de geologia do IFSP - Francisco César Dalmo (Confins)
The present work aims to present a description of the fieldwork in the discipline of Geology and Uses of Energy Sources, carried out by students of the Geography Teaching degree course at the Federal Institute of São Paulo (IFSP). The work was coordinated by two course instructors, who were responsible for providing explanations at each visited location regarding the local geology and other geography-related topics. During the site visits, students were able to clarify doubts about the visited locations with the teachers, as well as take photographic records that allowed the preparation of a report for the purpose of assessing the discipline. In addition to the information noted in the field, complementary bibliographies, photographs, and images were used. Finally, the execution of the fieldwork allowed for the expansion of knowledge about the discipline of geology and the understanding of the geological dynamics encompassing this region of the state of São Paulo and the global geological dynamics.